State minimum wage and mental health in the United States: 2011-2019 - Masanori Kuroki (Elsevier, 2021)
Consistent with a rise in "deaths of despair" (drug overdose, alcoholism, and suicide), the percentage of Americans reporting major mental and emotional problems in all 30 of the last 30 days has been increasing. Based on the hypothesis that this rise in extreme levels of distress is driven partly by financial hardships, this study investigates whether higher state minimum wages reduce the likelihood of extreme levels of distress among low-income, prime-age Americans with no postsecondary education. By matching state minimum wages with individual-level data from the 2011-2019 Behavioral Risk Factor Surveillance System, this study finds that a ten percent increase in the minimum wage is associated with a 0.4-0.5 percentage-point decline in the likelihood of extreme distress. The finding is consistent with the notion that growing extreme distress is attributable to despair driven by economic hardships and financial strain.